Nigeria and Cameroon under colonial rule, in Government reports, 1887-1962. - Great Britain. Foreign and Commonwealth Office (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
The Annual Departmental Reports relating to Nigeria and British Cameroons are a complementary collection to the earlier British Online Archives publication of Nigerian Blue Books. For the purpose of organisation, the departmental reports have been divided between ten headings: Administration, Finance, Judicial and Police, Natural Resources, Social Services, Transport and Public Works, Communications and Post Office Savings, Commerce, Miscellaneous, and reports relating to the British Cameroons. Within each section, departmental series have been organised in chronological order, prefaced by selected extraordinary reports and sessional papers of particular relevance, and followed by related sub-collections. The coverage of these reports changed as political conditions dictated, commencing with coverage of the Colony and Protectorate of Lagos in 1887. In 1906 Lagos was united with the Protectorate of Southern Nigeria to become the Colony and Protectorate of Southern Nigeria. The next administrative upheaval would occur in 1914, when the Colony and Protectorate of Southern Nigeria was amalgamated with the British Protectorate of Northern Nigeria, to form the Colony and Protectorate of Nigeria. The organisation of the Colony and Protectorate of Nigeria into provinces commenced in 1937; however, some departments were not subject to this change until the introduction of the 'MacPherson Constitution' of 1951. Further information on the history of Nigeria and of these reports in relation to it can be found in the guide to the microfilm edition, of which this collection is a digital copy.The Annual Departmental Reports relating to Nigeria and British Cameroons are a complementary collection to the earlier British Online Archives publication of Nigerian Blue Books. For the purpose of organisation, the departmental reports have been divided between ten headings: Administration, Finance, Judicial and Police, Natural Resources, Social Services, Transport and Public Works, Communications and Post Office Savings, Commerce, Miscellaneous, and reports relating to the British Cameroons. Within each section, departmental series have been organised in chronological order, prefaced by selected extraordinary reports and sessional papers of particular relevance, and followed by related sub-collections. The coverage of these reports changed as political conditions dictated, commencing with coverage of the Colony and Protectorate of Lagos in 1887. In 1906 Lagos was united with the Protectorate of Southern Nigeria to become the Colony and Protectorate of Southern Nigeria. The next administrative upheaval would occur in 1914, when the Colony and Protectorate of Southern Nigeria was amalgamated with the British Protectorate of Northern Nigeria, to form the Colony and Protectorate of Nigeria. The organisation of the Colony and Protectorate of Nigeria into provinces commenced in 1937; however, some departments were not subject to this change until the introduction of the 'MacPherson Constitution' of 1951. Further information on the history of Nigeria and of these reports in relation to it can be found in the guide to the microfilm edition, of which this collection is a digital copy.
Date range: 1887-1962.
Keywords: Nigeria -- Politics and government -- 20th century; Cameroon -- Politics and government -- 1884-1916.; Cameroon -- Politics and government -- 20th century